Fostering Social Interaction Variability in the Metaverse: A Case Study of the Museum of L’Avesnois in Fourmies - Makram Mestiri; Meriem Khadhar; Arnaud Huftier; Amos Fergombe (Heritage)
This study explores the transformative potential of the metaverse in redefining cultural heritage engagement, with a specific focus on the digital metamorphosis of the Museum of L’Avesnois in Fourmies. By leveraging advanced 3D scanning technologies and immersive virtual environments, select artifacts have been meticulously digitized, creating an unprecedented interactive platform that bridges accessibility gaps and invites global audiences to engage with cultural heritage. Variability in user experience, reflecting the diverse interactions, emotions, and cognitive responses of participants, serves as a critical analytical axis in this research. While diversity can yield invaluable insights into user preferences, excessive discrepancies risk fragmenting the coherence of engagement. This study demonstrates how strategic design interventions can mitigate such variability, fostering uniform yet personalized experiences. Through the integration of real-time social dynamics, enabled by customizable avatars and communication tools, the metaverse is established as a pioneering medium for collaborative cultural exploration. Employing a robust mixed-methods approach, this research synthesizes quantitative metrics with qualitative insights from in-depth interviews to critically evaluate the metaverse’s capacity to deliver authentic, emotionally resonant, and pedagogically impactful engagements. While challenges persist in replicating the emotive depth of physical exhibits and sustaining user attention, findings underscore the metaverse’s unparalleled efficacy in democratizing access to cultural artifacts and enabling transboundary social interactions. Furthermore, the seamless incorporation of previously inaccessible artifacts into these virtual domains significantly enhances both user engagement and educational outcomes. This work advances the discourse on digital heritage by presenting actionable insights into the design of virtual environments that uphold cultural authenticity, foster socially immersive interactions, and align with the broader paradigm of digital transformation.